Valorizing human capital for dynamic organizations through the triad of training-competency modeling-participation - Polo, Federica (Vaasan yliopisto, 2020)
Organizations operating in a business environment, characterized by market changes and knowledge-based competition, need to develop capabilities to accumulate, integrate and renew knowledge and resources in order to remain competitive. However, these capabilities are difficult to achieve because they are held back by people, groups and the organization itself, which together constitute the human capital (HC) of the organization. This dissertation focuses on the HC and, in particular, on companies’ investment in strategic HR practices to develop higher level and unique HC, best aligned with their strategic needs. Research to date lacks models able to examine how HR practices lead to HC development within organizations and which mechanisms play an important role in HC development in a business environment characterized by change. Therefore, the objective of this study is to understand how HR practices favor and contribute to HC development in changing organizations. To achieve this goal, this dissertation analyzes three main HR practices as the microfoundations of HC development: 1) the definition and development of competencies as a strategic tool to align individual competencies to organizational targets; 2) the role of a training culture in encouraging employees to update competencies and 3) the participation of employees in organizational restructuring as a key practice in aligning HR to the new business needs. The three practices are analyzed through the five articles included in this dissertation. From the methodological standpoint, this dissertation develops ad hoc tools that organizations can implement to sense, seize and reconfigure internal resources in order to develop HC and remain competitive in a changing business environment. This study contributes to the literature and practice by proposing a new conceptualization of HC as a dynamic capability and showing how the implementation of HR practices in a changing environment give leverage for HC development within organizations to generate uniqueness and meet business objectives through employees.

Muuttuvassa ja kilpaillussa liiketoimintaympäristössä toimivien organisaatioiden on kehitettävä kyvykkyyksiä tiedon ja resurssien keräämiseen, integrointiin ja uusimiseen kilpailukyvyn säilyttämiseksi. Näitä kyvykkyyksiä on kuitenkin vaikea saavuttaa, sillä henkilöt, ryhmät ja itse organisaatio, jotka yhdessä muodostavat organisaation inhimillisen pääoman, jarruttavat kehitystä. Tämä väitöskirja keskittyy inhimilliseen pääomaan ja erityisesti yritysten investointeihin strategisiin HR-käytäntöihin, joilla kehitetään korkeatasoista, ainutlaatuista ja yrityksen strategisiin tarpeisiin parhaiten sopivaa inhimillistä pääomaa. Tähänastisesta tutkimuksesta puuttuu malleja, joilla voitaisiin selvittää, miten HR-käytännöt johtavat inhimillisen pääoman kehitykseen organisaatioiden sisällä ja mitkä mekanismit ovat tärkeitä inhimillisen pääoman kehityksessä muuttuvissa liiketoimintaympäristössä. Tutkimuksen tavoitteena onkin ymmärtää, miten HR-käytännöt suosivat ja edistävät inhimillisen pääoman kehitystä muuttuvissa organisaatioissa. Väitöskirjassa analysoidaan kolmea HR-käytäntöä inhimillisen pääoman kehityksen mikroperustana: 1) osaamisen määritteleminen ja kehittäminen strategisena välineenä yksilöllisen osaamisen kohdistamiseksi organisaation tavoitteisiin, 2) koulutuskulttuurin rooli työntekijöiden rohkaisemisessa päivittämään osaamistaan ja 3) työntekijöiden osallistuminen organisaatiojärjestelyihin keskeisenä käytäntönä HR: n mukauttamisessa uusiin liiketoiminnan tarpeisiin. Kolmea käytäntöä analysoidaan viiden artikkelin avulla. Metodologisesti väitöskirja kehittää ad hoc -työkaluja, joita organisaatiot voivat käyttää sisäisten resurssien havaitsemiseen, hyödyntämiseen ja uudelleenjärjestelyyn inhimillisen pääoman kehittämiseksi ja kilpailukyvyn säilyttämiseksi muuttuvassa liiketoimintaympäristössä. Väitöskirja tukee kirjallisuutta ja käytäntöä ehdottamalla inhimillisen pääoman uutta käsitteellistämistä dynaamisena kyvykkyytenä sekä osoittamalla, miten HR-käytäntöjen käyttöönotto muuttuvassa ympäristössä vauhdittaa inhimillisen pääoman kehittämistä organisaatioissa luoden ainutlaatuisuutta sekä saavuttaakseen liiketoiminnan tavoitteet työntekijöiden kautta.
Dynaamisten organisaatioiden inhimillisen pääoman hyödyntäminen harjoittelun, osaamisen mallintamisen ja osallistumisen kautta
Keywords: HR practices; dynamic capability; human capital; competency modelling; training; organizational restructuring; henkinen pääoma; organisaatiot; johtaminen; dynaamiset kyvykkyydet; fi=Tuotantotalous|en=Industrial Management|